Bringing out the Hidden Value of Marine Ecosystem Services in Xàbia (Spain): An Economic Valuation via Multicriteria Analysis - Gómez-Aguayo, Ana M.; Estruch-Guitart, Vicente; Torner-Orellana, Francisco; Ferrando, M. J. (Journal of Environmental Accounting and Management, 2026)
The current threats and deterioration of the coastal marine ecosystem require the scientific dissemination of their natural values in order to achieve immediate action by policy makers. The western marine areas of the Mediterranean present habitats that are unknown to most stakeholders, and their contribution to the well-being is difficult to identify. Thus, we have proposed an estimation of the economic value of the Ecosystem Services (ESs) in the marine coastal strip of Xàbia, north of Alicante, Spain. We conducted 14 face-to-face structured interviews with local experts with backgrounds in marine areas. We used the Analytic Network Process (ANP) to identify essential ESs in the mapped area. Participants identified as relevant a set of seven ESs (seafood, habitat services, climate regulation, waste treatment, biological control, recreation, and knowledge development). Using the Discounted Cash Flow method, we obtained the monetary value of each ESs. Our results reveal that one-third of the total value of the ecosystem corresponds to habitat services (e.g., life cycle maintenance, gene pool protection), whose major contribution is supporting waste treatment and biological control functions of the ecosystem. Our findings will provide useful information for marine management decisions and could enhance territorial conservation policies.